ANALISIS SISTEM PENGENDALIAN INTERNAL KAS PADA PT. BANK NASIONAL INDONESIA (BNI) - PARLIN P LINGGA, RAYKARD (Jurnal Akuntansi AKUNESA, 2013)
Cash is a form of assets, that is very valuable for the smooth operation of thebanking. Whereas, the controlling internal system are very affecting for theoperational management system in the banking activity, specially cash. If thecontrolling internal system was broken, so the banking activity will be disturbedand it will be affected the performance of the banking. The purpose of the study isfinding out of Controlling Internal System in the Indonesia banking. The bankingis National Indonesia Bank (BNI).Keywords : cash, controlling internal system, banking